Peripheral Nerve Innervation in Bilateral Cleft Hand Syndrome Elucidated by Ultrasound - Falco, Pietro; Hovius, Steven; van Alfen, Nens (Frontiers in Neurology, 2022)
Bilateral cleft hand syndrome is a rare congenital malformation with complex anatomy. Previous reports have mainly focused on the description of bone and soft tissue abnormalities, but information about innervation is scarce. Knowledge of the peripheral nerve anatomy is helpful for surgical treatment, optimizing the reconstruction, and preventing iatrogenic damage. Following clinical assessment and conventional radiologic imaging, we used high-resolution ultrasound of both hands and forearms to image the peripheral nerves in a patient with severe bilateral cleft hand syndrome. The patient presented with two ulnar digits, a deformed thumb on the right, and a rudimentary thumb appendage on the left. In keeping with the tissue elements present and absent, we found a severe bilateral nerve size reduction of the median nerves, sparing the anterior interosseous nerve fascicles. The radial nerve and end branches were intact, and a slightly smaller ulnar nerve was found that ended in two digital branches to a single digit. Our study shows that in cleft hand syndrome the peripheral nervous system anatomy exactly reflects the presence and absence of the corresponding muscle and skin innervation areas. This information is helpful for planning a surgical-reconstructive approach and suggests a potential role for nerve ultrasound in the assessment of complex limb malformations.